Single-Pixel Photon-Counting Imaging Based on Dual-Comb Interferometry - Hu, Huiqin (Nanomaterials (Basel), 2021)
We propose and experimentally demonstrate single-pixel photon counting imaging based on dual-comb interferometry at 1550 nm. Different from traditional dual-comb imaging, this approach enables imaging at the photon-counting regime by using single-photon detectors combined with a time-correlated single-photon counter to record the returning photons. The illumination power is as low as 14 pW, corresponding to 2.2 × 10(−3) photons/pulse. The lateral resolution is about 50 μm. This technique paves the way for applying dual-comb in remote sensing and imaging.